NDUFA4L2 protects against ischaemia/reperfusion‐induced cardiomyocyte apoptosis and mitochondrial dysfunction by inhibiting complex I. (July 2017) - Li, Jianhua; Bai, Caiyan; Guo, Junxia; Liang, Wanqian; Long, Jingning
Summary: Myocardial ischaemia/reperfusion (I/R) injury may cause the apoptosis of cardiomyocytes as well as mitochondrial dysfunction. The aims of the present study were to investigate whether NADH dehydrogenase 1 alpha subcomplex subunit 4‐like 2 (NDUFA4L2) on myocardial ischaemia‐reperfusion (I/R) injury and the underlying molecular mechanism. The hypoxia‐reperfusion (H/R) model was established in vitro using H9c2 cells to simulate I/R injury. NDUFA4L2 and complex I expression levels were detected using RT‐PCR and western blot. The apoptosis of H9c2 cells was evaluated by flow cytometry and the expression of Bax and Bcl‐2 was detected by western blot. The mitochondrial function was assessed by ATP concentration, mPTP opening and cytochrome c (cyto C) expression. Our data indicated that NDUFA4L2 expression was significantly down‐regulated in myocardial H/R injury. Overexpression of NDUFA4L2 led to a dramatic prevention of H/R‐induced apoptosis accompanied by a decrease in the expression of Bax and an increase in the expression of Bcl‐2. Meanwhile, augmentation of NDUFA4L2 dramatically prevented mitochondrial dysfunction caused by H/R as reflecting in the increased ATP concentration, delayed mPTP opening, as well as down‐regulated cyto C expression. Moreover, complex I activation was heightened and negatively regulated by NDUFA4L2. Silencing complex I conspicuously attenuated cell apoptosis and mitochondrial dysfunction. Taken together, our findings demonstrated that NDUFA4L2 protects against H/R injury by preventing myocardium apoptosis and mitochondrial dysfunction via the complex I, and may be a potential therapeutic approach for attenuating myocardial I/R injury.